Cultural Guidelines for Commercial Production of Interiorscape ZZ (Zamioculcas zamiifolia) - Jianjun Chen; Richard J. Henny; Dennis B. McConnell (EDIS, 2005)
This article is intended to provide brief guidelines for propagation, production, and interior use of 'ZZ' plant (Zamioculcas zamiifolia). This document is ENH997, a series of the Environmental Horticulture Department, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: December 2004. Reviewed: April 2005.